Platinum-cobalt alloy grade hole doped carbon catalyst for fuel cell and preparation method of platinum-cobalt alloy grade hole doped carbon catalyst

By calcining and wet reduction on cobalt nitrogen co-doped carbon materials at high temperature and wet reduction, fine platinum-cobalt alloy nanoparticles are generated, solving the problems of slow kinetics, poor stability and high cost in fuel cells, and the preparation and industrial production of platinum-cobalt alloy catalysts with high catalytic activity and stability are achieved.

CN119852432AActive Publication Date: 2025-04-18SHANGHAI JIAOTONG UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510049967.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Existing platinum-based catalysts have problems such as slow kinetics, poor stability and high cost in proton exchange membrane fuel cells, which are difficult to synthesize and apply on a large scale in industrial practice.

Method used

By high-temperature calcination and wet reduction methods, fine platinum-cobalt alloy nanoparticles are generated on the surface of cobalt nitrogen co-doped carbon material, and a platinum-cobalt alloy catalyst with high catalytic activity and stability is prepared.

Benefits of technology

High catalytic activity and long-term stability of platinum-cobalt alloy catalysts are achieved, process steps are simplified, and large-scale production under industrial conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852432A_ABST
    Figure CN119852432A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heterojunction electro-catalysis fuel cells, and particularly discloses a platinum-cobalt alloy grade hole doped carbon catalyst for a fuel cell and a preparation method of the platinum-cobalt alloy grade hole doped carbon catalyst. The platinum-cobalt alloy is formed by calcining a porous carbon material, nitrogen-containing organic molecules and a cobalt source and further reducing a platinum source through a wet method. According to the method, nitrogen-containing small organic molecules are introduced to form micropore-mesopore-macropore grade pore structure modification on the porous carbon material, and meanwhile, cobalt nanoparticles are uniformly pre-embedded in the porous carbon material, so that the interaction between the carrier and metal particles is improved; a platinum source and cobalt nanoparticles form alloy nanoparticles through wet impregnation reduction, so that uniform distribution of superfine alloy nanoparticles and prolonging of the stability and the service life of the catalyst are realized. As a novel catalyst, the platinum-cobalt alloy catalyst disclosed by the invention has wide application potential in oxygen reduction reaction, is simple in preparation process, safe, green and low in cost, and can meet the requirements of large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of heterojunction electrocatalytic fuel cells and relates to a platinum-cobalt alloy heterojunction structure oxygen reduction reaction catalyst, and specifically relates to a platinum-cobalt alloy hierarchical pore doped carbon catalyst for fuel cells and a preparation method thereof. Background Art

[0002] The increasingly serious energy shortage caused by the accelerated consumption of traditional fossil energy and the resulting climate problems urgently require the development of green and sustainable energy and energy conversion devices. Green and cheap hydrogen energy and its devices, hydrogen fuel cells, have naturally attracted widespread attention. Proton exchange membrane fuel cells (PEMFCs) have the advantages of high power density, high energy conversion efficiency, low operating temperature, fast startup, good stability, and environmental friendliness, and have great potential in solving energy and climate problems.

[0003] Catalyst is one of the core materials of PEMFC and has a significant impact on the production cost, energy conversion efficiency and battery life of fuel cells. However, slow kinetics is a major limitation to the further development of PEMFC, so it is crucial to develop ORR catalysts with high catalytic activity and high stability. Platinum and platinum-based materials are still the electrocatalysts with the best performance in oxygen reduction reaction. Despite their wide application, the low tolerance, poor stability and high cost of platinum-based catalysts to small molecules such as methanol, carbon monoxide and phosphoric acid limit their further development and application in proton exchange membrane fuel cells. Alloying platinum with non-precious metals to form alloys or core / shell structures is the mainstream means to reduce the cost of platinum-based catalysts and improve the catalytic performance of oxygen reduction reaction. Alloying can not only improve the utilization efficiency of platinum, but also optimize the adsorption strength of oxygen-containing intermediates through potential ligand / strain effects. In addition to alloying, the combination of several typical strategies such as increasing the exposure of surface active atoms, defect engineering and local coordination optimization can also effectively improve the utilization of platinum.

[0004] Although efficient utilization of platinum and reduced consumption of platinum have been achieved, the good results of these platinum catalysts are often not reproduced in industrial practice. In addition, these complex and precise surface modification strategies often cannot provide large-scale industrial synthesis of gram-scale catalysts, which is still a very challenging problem in actual production.

[0005] Based on the above points, the present invention focuses on platinum-cobalt alloy catalysts, aiming to prepare on a large scale platinum-cobalt alloy catalysts that amplify the catalytic activity of platinum with transition metals. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a platinum-cobalt alloy catalyst for oxygen reduction reaction, which is prepared by high-temperature calcination and wet reduction to generate fine platinum-cobalt alloy nanoparticles on the surface of cobalt-nitrogen co-doped carbon material. The synthesis method of this platinum-cobalt alloy catalyst is simple, the industrial preparation conditions are mature, and it has good electrochemical properties.

[0007] The specific technical solution adopted by the present invention is as follows:

[0008] In a first aspect, the present invention provides a method for preparing a platinum-cobalt alloy hierarchical pore-doped carbon catalyst for a fuel cell, comprising the following steps:

[0009] (1) mixing a porous carbon material, a cobalt source, and a nitrogen-containing organic small molecule uniformly, and then calcining to obtain a cobalt-nitrogen co-doped carbon material having a microporous-mesoporous-macroporous hierarchical pore structure; acid-washing the material powder, filtering, and drying;

[0010] (2) The cobalt-nitrogen co-doped carbon material is dispersed in water by ultrasound and stirring, a platinum source solution is added to the solution containing the cobalt-nitrogen co-doped carbon material, the pH value is adjusted, and the carbon material is reduced with a reducing agent by a wet impregnation reduction method; the product is washed and dried, and the obtained sample is a platinum-cobalt alloy catalyst.

[0011] Furthermore, in step (1), the porous carbon material includes but is not limited to one of activated carbon, XC-72, XC-72R, BP2000 and Super P Li, preferably XC-72R.

[0012] Furthermore, in step (1), the cobalt source includes but is not limited to one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, and cobalt sulfate, preferably cobalt chloride hexahydrate.

[0013] Furthermore, in step (1), the nitrogen-containing organic small molecule includes but is not limited to one or more of dicyandiamide, triethylenediamine, 1,10-phenanthroline, cucurbituril, 1,4,7,10-tetraazacyclododecane, aza-18-crown-6 and tetraphenylporphyrin, preferably aza-18-crown-6 and cucurbituril.

[0014] Furthermore, in step (1), the molar ratio of the cobalt source to the nitrogen-containing organic small molecule satisfies the coordination number of cobalt, preferably 1:2 (this ratio can ensure complete coordination under the selection of the above cobalt source and nitrogen-containing organic small molecule species).

[0015] Furthermore, in step (1), the calcination temperature is 800-1200° C., preferably 900° C.; the calcination is carried out under a protective atmosphere, and the protective atmosphere is an inert gas, including but not limited to one of argon, nitrogen and helium, preferably nitrogen.

[0016] Furthermore, in step (1), the cobalt-nitrogen co-doped carbon material is pickled using one of the solutions including but not limited to sulfuric acid, nitric acid, and perchloric acid, preferably a perchloric acid solution; the acid concentration is controlled at 1-2 mol / L, preferably 1 mol / L; the pickling time is 12-24 h, preferably 12 h.

[0017] Furthermore, in step (2), the platinum source includes but is not limited to one of platinum nitrate, tetraammine platinum nitrate, platinum chloride, chloroplatinic acid hexahydrate, potassium chloroplatinate, sodium chloroplatinate and platinum acetylacetonate, preferably platinum nitrate.

[0018] Furthermore, in step (2), the pH is adjusted by an alkaline solution, wherein the alkaline solution includes but is not limited to one of sodium hydroxide and potassium hydroxide, preferably sodium hydroxide; the pH value of the solution is in the range of 12-14, preferably 13.

[0019] Furthermore, in step (2), the reducing agent includes but is not limited to one of sodium borohydride, ethylene glycol and polyvinyl pyrrolidone, preferably sodium borohydride.

[0020] In a second aspect, the present invention provides a platinum-cobalt alloy grade pore-doped carbon catalyst for a fuel cell prepared by the above preparation method.

[0021] Furthermore, in the platinum-cobalt alloy catalyst, the mass percentage of platinum element is 0.0001-70wt%, and the mass percentage of cobalt element is 0.0001-50wt% (preferably 2-50wt%), wherein the ratio of platinum element to cobalt element can be arbitrarily adjusted by the ratio of metal sources.

[0022] Furthermore, in the platinum-cobalt alloy catalyst, the particle size of the metal nanoparticles is between 1.2 nm and 4.2 nm.

[0023] The present invention has the following beneficial effects:

[0024] 1. The platinum-cobalt alloy catalyst of the present invention can be made into an electrode, has high catalytic activity in a fuel cell and its catalytic performance remains stable for a long time.

[0025] 2. The present invention prepares a platinum-cobalt alloy heterojunction structure by high-temperature calcination and wet reduction. The synthesis method has the characteristics of simple process, green and safe, easy control, good activity and stability of the catalyst, and can realize large-scale production and preparation.

[0026] 3. The platinum-cobalt alloy catalyst electrochemical catalyst developed by the present invention will not only have important applications in the fields of chemical industry and energy, but will also provide a new perspective for the research of electrocatalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the TEM image of the platinum-cobalt alloy catalyst prepared in Example 13 of the present invention.

[0028] Figure 2 This is a particle size distribution histogram of the platinum-cobalt alloy catalyst prepared in Example 13 of the present invention.

[0029] Figure 3 This is the PXRD pattern of the platinum-cobalt alloy catalyst prepared in Example 13 of the present invention.

[0030] Figure 4 2 is the LSV diagram of Example 13 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0031] In view of the problems that the existing preparation methods of platinum-cobalt alloy catalysts are complicated, difficult to reproduce in industrial practice, and cannot be synthesized on a large scale, the present invention provides a method for preparing platinum-cobalt alloy catalysts in two steps of high-temperature calcination and wet reduction. The method introduces nitrogen-containing organic small molecules in the calcination step to modify the structure of porous carbon materials to form micropores-mesopores-macroporous hierarchical pores, and at the same time, cobalt nanoparticles are uniformly pre-buried in the porous carbon material to improve the interaction between the carrier and the metal particles; through wet impregnation reduction, the platinum source and cobalt nanoparticles are further formed into alloy nanoparticles with freely adjustable proportions, and the strong interaction between platinum and cobalt and the anchoring effect of cobalt and the carrier are used to form a structure in which the concentration of cobalt elements increases from the alloy to the carrier, thereby achieving uniform distribution of ultrafine alloy nanoparticles and extending the stability and life of the catalyst. Therefore, while simplifying the process steps, the preparation quality of the platinum-cobalt alloy catalyst is guaranteed, and large-scale production and preparation can be achieved. The preparation method specifically includes the following steps:

[0032] (1) uniformly mixing a porous carbon material, a cobalt source, and a nitrogen-containing organic small molecule: the porous carbon material includes but is not limited to one of activated carbon, XC-72, XC-72R, BP2000, and Super P Li; the cobalt source includes but is not limited to one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, and cobalt sulfate; the nitrogen-containing organic small molecule includes but is not limited to one of dicyandiamide, triethylenediamine, 1,10-phenanthroline, cucurbit[7]uril, 1,4,7,10-tetraazacyclododecane, aza-18-crown-6, and tetraphenylporphyrin; the molar ratio of the cobalt source to the nitrogen-containing organic small molecule satisfies the coordination number of cobalt;

[0033] Then, a cobalt-nitrogen co-doped carbon material having a microporous-mesoporous-macroporous hierarchical pore structure is obtained by calcination: the calcination temperature is 800-1200° C.; the calcination is carried out under a protective atmosphere, and the protective atmosphere is an inert gas, including but not limited to one of argon, nitrogen and helium; the main factors affecting the formation of the microporous-mesoporous-macroporous hierarchical pore structure are the calcination temperature, the type of organic small molecules and the type of carbon material. The surface area and cobalt content of the carrier can be effectively adjusted by using different porous carbon materials, organic small molecules and calcination temperatures;

[0034] Then, the cobalt-nitrogen co-doped carbon material powder is pickled, filtered, and dried: the pickling solution includes but is not limited to one of sulfuric acid, nitric acid, and perchloric acid solution, the concentration is controlled at 1-2 mol / L, and the pickling time is 12-24 hours;

[0035] (2) dispersing the cobalt-nitrogen co-doped carbon material into water by ultrasonication and stirring, and adding a platinum source solution into the solution containing the cobalt-nitrogen co-doped carbon material, wherein the platinum source includes but is not limited to one of platinum nitrate, tetraammine platinum nitrate, platinum chloride, chloroplatinic acid hexahydrate, potassium chloroplatinate, sodium chloroplatinate and platinum acetylacetonate;

[0036] Then, the pH value is adjusted, and a wet impregnation reduction method is used to reduce the pH value with a reducing agent: the pH adjustment is adjusted by an alkaline solution, the alkaline solution includes but is not limited to one of sodium hydroxide and potassium hydroxide, and the pH value of the solution ranges from 12 to 14; the reducing agent includes but is not limited to one of sodium borohydride, ethylene glycol and polyvinyl pyrrolidone;

[0037] Finally, the product is washed and dried, and the obtained sample is a platinum-cobalt alloy catalyst. The factors affecting the quality of the catalyst product are mainly the ratio of the cobalt source, organic small molecules and carbon carriers and the calcination temperature, among which: the molar ratio of the cobalt source to the nitrogen-containing organic small molecules must meet the coordination number of cobalt, and the coordination ability and ratio of the organic molecules affect the pore structure of the carrier and the particle size of the cobalt particles; too high a cobalt content is not easy to form an alloy, and too low a content affects the adsorption capacity of platinum particles. It is more appropriate to control the cobalt content in the product to 2-50wt%; the calcination temperature affects the pore structure, the cobalt content and the particle size distribution. If the temperature is too low, the organic molecules are not completely decomposed, and if it is too high, the pore structure will collapse.

[0038] The following is a specific example of catalyst preparation according to the above method, which is used to further illustrate the present invention.

[0039] Example 1

[0040] Place 1g, 2.08g, 1.84g, 8.14g of XC-72R, cobalt chloride hexahydrate, aza-18-crown ether-6, cucurbit[7]uril, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The obtained cobalt-nitrogen co-doped carbon material is acid-washed, filtered, and dried. Add a solution containing 5850mg of platinum tetrachloride to 1g of cobalt-nitrogen co-doped carbon material and stir to reduce at room temperature. Wash and dry the product, and then reduce it with sodium borohydride at room temperature. Obtain a platinum-cobalt alloy catalyst.

[0041] Example 2

[0042] Place 1g, 1.04g, 0.92g, 4.07g of XC-72R, cobalt chloride hexahydrate, aza-18-crown ether-6, cucurbit[7]uril, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The obtained cobalt-nitrogen co-doped carbon material is acid-washed, filtered, and dried. Add a solution containing 5850mg of platinum tetrachloride to 1g of cobalt-nitrogen co-doped carbon material and stir and reduce at room temperature. Wash and dry the product, and then reduce it with sodium borohydride at room temperature. Obtain a platinum-cobalt alloy catalyst.

[0043] Example 3

[0044] Place 1g, 0.52g, 0.46g, 2.03g of XC-72R, cobalt chloride hexahydrate, aza-18-crown ether-6, cucurbit[7]uril, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The obtained cobalt-nitrogen co-doped carbon material is acid-washed, filtered, and dried. Add a solution containing 5850mg of platinum tetrachloride to 1g of cobalt-nitrogen co-doped carbon material and stir and reduce at room temperature. Wash and dry the product, and then reduce it with sodium borohydride at room temperature. Obtain a platinum-cobalt alloy catalyst.

[0045] Example 4

[0046] Place 1g, 0.26g, 0.23g, 1.02g of XC-72R, cobalt chloride hexahydrate, aza-18-crown ether-6, cucurbit[7]uril, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The obtained cobalt-nitrogen co-doped carbon material is acid-washed, filtered, and dried. Add a solution containing 5850mg of platinum tetrachloride to 1g of cobalt-nitrogen co-doped carbon material and stir to reduce at room temperature. Wash and dry the product, and then reduce it with sodium borohydride at room temperature. Obtain a platinum-cobalt alloy catalyst.

[0047] Example 5

[0048] 1g, 0.29g, 0.26g, 1.16g of Super P, cobalt chloride hexahydrate, aza-18-crown ether-6, cucurbit[7]uril, 240ml of deionized water and 180ml of acetonitrile mixture were placed in a beaker and heated at 70°C until the water was completely evaporated. The obtained solid powder was calcined under nitrogen protection at a calcination temperature of 800°C. The obtained cobalt-nitrogen co-doped carbon material was acid-washed, filtered and dried. A solution containing 5850mg of platinum tetrachloride was added to 1g of cobalt-nitrogen co-doped carbon material and stirred for reduction at room temperature. The product was washed and dried, and then reduced with sodium borohydride at room temperature. A platinum-cobalt alloy catalyst was obtained.

[0049] Example 6

[0050] BP2000, cobalt chloride hexahydrate, aza-18-crown ether-6, cucurbit[7]uril, 240ml deionized water and 180ml acetonitrile mixture with masses of 1g, 0.73g, 0.66g and 2.91g respectively were placed in a beaker and heated at 70°C until the water was completely evaporated. The obtained solid powder was calcined under nitrogen protection at a calcination temperature of 800°C. The obtained cobalt-nitrogen co-doped carbon material was acid-washed, filtered and dried. A solution containing 5850mg of platinum tetrachloride was added to 1g of cobalt-nitrogen co-doped carbon material and stirred for reduction at room temperature. The product was washed and dried, and then reduced with sodium borohydride at room temperature. A platinum-cobalt alloy catalyst was obtained.

[0051] Example 7

[0052] Place 1g, 0.40g, 0.46g, 2.03g of XC-72R, hexahydrated cobalt nitrate, aza-18-crown ether-6, cucurbit[7]uril, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The obtained cobalt-nitrogen co-doped carbon material is acid-washed, filtered, and dried. Add a solution containing 5850mg of platinum tetrachloride to 1g of cobalt-nitrogen co-doped carbon material and stir and reduce at room temperature. Wash and dry the product, and then reduce it with sodium borohydride at room temperature. Obtain a platinum-cobalt alloy catalyst.

[0053] Example 8

[0054] Place 1g, 0.61g, 0.46g, 2.03g of XC-72R, cobalt sulfate, aza-18-crown ether-6, cucurbit[7]uril, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The obtained cobalt-nitrogen co-doped carbon material is acid-washed, filtered, and dried. Add a solution containing 5850mg of platinum tetrachloride to 1g of cobalt-nitrogen co-doped carbon material and stir and reduce at room temperature. Wash and dry the product, and then reduce it with sodium borohydride at room temperature. Obtain a platinum-cobalt alloy catalyst.

[0055] Example 9

[0056] Place 1g, 0.52g, 0.24g, 0.20g of XC-72R, cobalt chloride hexahydrate, dicyandiamide, triethylenediamine, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The resulting cobalt-nitrogen co-doped carbon material is acid-washed, filtered, and dried. A solution containing 5850mg of platinum tetrachloride is added to 1g of cobalt-nitrogen co-doped carbon material and stirred at room temperature for reduction. The product is washed and dried, and then reduced with sodium borohydride at room temperature. A platinum-cobalt alloy catalyst is obtained.

[0057] Example 10

[0058] Place 1g, 0.52g, 0.24g, 0.31g of XC-72R, cobalt chloride hexahydrate, dicyandiamide, 1,10-phenanthroline, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The obtained material is a cobalt-nitrogen co-doped carbon material, which is acid-washed, filtered and dried. A solution containing 5850mg of platinum tetrachloride is added to 1g of cobalt-nitrogen co-doped carbon material and stirred at room temperature for reduction. The product is washed and dried, and then heated to 120°C with ethylene glycol for reduction. A platinum-cobalt alloy catalyst is obtained.

[0059] Embodiment 11

[0060] Place 1g, 0.52g, 0.71g of XC-72R, cobalt chloride hexahydrate, 1,4,7,10-tetraazacyclododecane, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The obtained material is a cobalt-nitrogen co-doped carbon material, which is acid-washed, filtered, and dried. A solution containing 5850mg of platinum tetrachloride is added to 1g of cobalt-nitrogen co-doped carbon material and stirred at room temperature for reduction. The product is washed and dried, and then heated to 120°C with ethylene glycol for reduction. A platinum-cobalt alloy catalyst is obtained.

[0061] Example 12

[0062] Place 1g, 0.52g, 1.08g of XC-72R, cobalt chloride hexahydrate, tetraphenylporphyrin, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 800°C. The obtained material is a cobalt-nitrogen co-doped carbon material, which is acid-washed, filtered and dried. A solution containing 5850mg of platinum tetrachloride is added to 1g of cobalt-nitrogen co-doped carbon material and stirred at room temperature for reduction. The product is washed and dried, and then heated to 120°C with ethylene glycol for reduction. A platinum-cobalt alloy catalyst is obtained.

[0063] Example 13

[0064] Place 1g, 0.52g, 0.46g, 2.03g of XC-72R, cobalt chloride hexahydrate, aza-18-crown ether-6, cucurbit[7]uril, 240ml of deionized water and 180ml of acetonitrile mixture in a beaker, heat at 70°C until the water is completely evaporated, and calcine the obtained solid powder under nitrogen protection at a calcination temperature of 900°C. The obtained cobalt-nitrogen co-doped carbon material is acid-washed, filtered, and dried. Add a solution containing 5850mg of platinum tetrachloride to 1g of cobalt-nitrogen co-doped carbon material and stir at room temperature for reduction. Wash and dry the product, and then heat it at 80°C with polyvinyl pyrrolidone for reduction. Obtain a platinum-cobalt alloy catalyst.

[0065] Comparative Example 1: Preparation of Commercial Platinum Carbon Electrode

[0066] This comparative example uses the commercial precious metal platinum, which is widely studied at present, to prepare the electrode, and compares the performance with Example 13. The specific operation is as follows: grind the commercial platinum carbon with a mass fraction of 40% purchased from the chemical platform, take 2 mg and add it to a glass bottle, then add 0.40 mL ultrapure water, 0.50 mL isopropanol and 0.1 mL 5% nafion solution, ultrasonically form ink, take 0.005 mL of ink and drop it on the rotating disk electrode, and dry it naturally. The platinum-cobalt alloy catalyst prepared in Example 13 is also prepared according to the same operation.

[0067] The platinum-cobalt alloy catalyst prepared in Examples 1-13 has uniform alloy particle size and is uniform on the carrier, and the cobalt content is in the range of 5-40wt%, and the catalyst has good catalytic activity and electrochemical stability. The following is the observation and evaluation results of the platinum-cobalt alloy catalyst obtained in Example 13.

[0068] Figure 1 This is the TEM image of the platinum-cobalt alloy catalyst prepared in Example 13. It can be seen that the carrier still retains the basic morphology of the porous carbon material before calcination and the alloy nanoparticles are evenly distributed on the carrier.

[0069] Figure 2 This is the particle size distribution histogram of the platinum-cobalt alloy catalyst prepared in Example 13. It can be seen that the size of the nanoparticles is uniform and concentrated at 2.7 nm.

[0070] Figure 3 The PXRD pattern of the platinum-cobalt alloy catalyst prepared in Example 13 shows that the diffraction peaks of the synthesized catalyst are consistent with those of the standard platinum-cobalt alloy, proving that the nanoparticles supported thereon are indeed platinum-cobalt alloy. The half-peak width of the main diffraction peak indicates that the crystal size is relatively small.

[0071] Figure 4The LSV diagram of the electrode made of the catalyst of Example 13 and Comparative Example 1 shows that the half-wave potential, active mass and limiting current of Example 13 are better than those of commercial platinum carbon, proving that its ORR performance is better than that of commercial platinum carbon. Specifically, the limiting current density of Example 13 is 5.9 mA / cm 2 , the half-wave potential is 0.89V; the limiting current density of comparative example 1 is 5.6mA / cm 2 , the half-wave potential is 0.88V; the active mass is a normalized comparable value obtained by dividing the exchange current density at 0.9V by the platinum content in the catalyst, and Example 13 is 0.5A / mg Pt , Comparative Example 1 is 0.2A / mg Pt .

[0072] This specific implementation is only an explanation of the present invention, not a limitation of the present invention. Any changes made by those skilled in the art after reading the specification of the present invention will be protected by the patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A method for preparing a platinum-cobalt alloy hierarchical pore-doped carbon catalyst for a fuel cell, characterized in that: The following steps are involved: (1) mixing a porous carbon material, a cobalt source, and a nitrogen-containing organic small molecule uniformly, and then calcining to obtain a cobalt-nitrogen co-doped carbon material having a microporous-mesoporous-macroporous hierarchical pore structure; acid-washing the material powder, filtering, and drying; (2) dispersing the cobalt-nitrogen co-doped carbon material into water by ultrasound and stirring, adding a platinum source solution to the solution containing the cobalt-nitrogen co-doped carbon material, adjusting the pH value, and reducing the solution with a reducing agent by a wet impregnation reduction method; The product was washed and dried, and the obtained sample was a platinum-cobalt alloy catalyst.

2. The method for preparing the platinum-cobalt alloy hierarchical pore-doped carbon catalyst for fuel cells according to claim 1, characterized in that: In step (1), the porous carbon material is one of activated carbon, XC-72, XC-72R, BP2000 and Super P Li; the cobalt source is one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate and cobalt sulfate; the nitrogen-containing organic small molecule is one or more of dicyandiamide, triethylenediamine, 1,10-phenanthroline, cucurbit[7]uril, 1,4,7,10-tetraazacyclododecane, aza-18-crown ether-6 and tetraphenylporphyrin.

3. The method for preparing the platinum-cobalt alloy hierarchical pore-doped carbon catalyst for fuel cells according to claim 1, characterized in that: In step (1), the molar ratio of the cobalt source to the nitrogen-containing organic small molecule satisfies the coordination number of cobalt.

4. The method for preparing the platinum-cobalt alloy hierarchical pore-doped carbon catalyst for fuel cells according to claim 1, characterized in that: In step (1), the calcination temperature is 800-1200° C., and the calcination is carried out under a protective atmosphere, which is an inert gas.

5. The method for preparing the platinum-cobalt alloy hierarchical pore-doped carbon catalyst for fuel cells according to claim 1, characterized in that: In step (1), the cobalt-nitrogen co-doped carbon material is pickled using one of sulfuric acid, nitric acid and perchloric acid solutions, the acid concentration is controlled at 1-2 mol / L, and the pickling time is 12-24 h.

6. The method for preparing the platinum-cobalt alloy hierarchical pore-doped carbon catalyst for fuel cells according to claim 1, characterized in that: In step (2), the platinum source is one of platinum nitrate, tetraammine platinum nitrate, platinum chloride, chloroplatinic acid hexahydrate, potassium chloroplatinate, sodium chloroplatinate and platinum acetylacetonate.

7. The method for preparing the platinum-cobalt alloy hierarchical pore-doped carbon catalyst for fuel cells according to claim 1, characterized in that: In step (2), in the wet impregnation reduction method, the pH value of the solution is adjusted to 12-14, and the reducing agent is one of sodium borohydride, ethylene glycol and polyvinyl pyrrolidone.

8. A platinum-cobalt alloy hierarchical pore-doped carbon catalyst for a fuel cell prepared by the preparation method according to any one of claims 1 to 7.

9. The platinum-cobalt alloy hierarchical pore-doped carbon catalyst for fuel cells according to claim 8, characterized in that: In the platinum-cobalt alloy catalyst, the mass percentage of platinum element is 0.0001-70wt%, and the mass percentage of cobalt element is 0.0001-50wt%, wherein the ratio of platinum element to cobalt element can be arbitrarily adjusted by the ratio of metal sources.

10. The platinum-cobalt alloy hierarchical pore-doped carbon catalyst for fuel cells according to claim 8, characterized in that: In the platinum-cobalt alloy catalyst, the particle size of the metal nanoparticles is between 1.2nm and 4.2nm.

Citation Information

Patent Citations

  • Platinum-loaded nitrogen phosphorus co-doped carbon material hydrogen evolution catalyst, preparation method and application thereof

    CN107623134A

  • Iron and nitrogen co-doped carbon oxygen reduction catalyst and preparation method thereof

    CN110534752A

  • Novel Pt-Co / NC catalyst and preparation method and application thereof

    CN111987322A

  • Preparation method of cobalt-modified carbon-supported superfine platinum nano-alloy catalyst

    CN113422073A

  • Platinum-based nano heterogeneous material and preparation method thereof

    CN115505954A